Factorial confirmatory analysis to measure the perception of labor inclusion of people with disabilities - Saúl Pérez-Hernández (Universidad De La Salle Bajío, 2021)
Introduction: The objective of this scientific approach was to validate through confirmatory factor analysis a measurement model to determine the perceived importance of the inclusion of persons with disabilities in the labor market, in employees who work or interact during the course of their duties with disabled employees.